Nexo causal no acidente de trabalho - Cabral, Lenz Alberto Alves (2017)
Establishing causal connections in occupational accidents is essential to ensure the rights and duties of employees, employers, and the government. Nevertheless, lack of consensus in the performance of this task is common in labor claims. Objective: to compare causal connections established by the SEMST (Specialized Services in Safety Engineering and Occupational Medicine), the INSS (National Social Security Institute) and the Labor Court in 71 labor claims with sentences already handed down. Methods: this was a quantitative data analysis study with a documental, descriptive, analytical and reflexive design, which aimed to identify similarities and differences between the causal connections established by the three institutions (SESMT, INSS, and Labor Court) responsible for this task. Our goal was to characterize legitimate occupational accidents and distinguish them from events that cannot be characterized as legitimate. We searched the Brazilian Labor Legislation to identify what is an “occupational accident”, who is responsible for its characterization, which legal and technical criteria are used by each responsible institution, and what are the main causes of differences and coincidences between the three conclusions drawn. We also analyzed 71 labor claims with sentences already handed down in 2014 by judges of a labor court and compared the three causation connections established by the SESMT, Social Security and the Labor Court for the same labor claim. We verified whether the causal connections were positive or negative, registering agreement and noting the justifications in cases of differences between them. Results: our bibliographical search revealed that agreement between the three institutions is due to law 8213 being used by each of them to legally support the characterization of occupational accidents. Differences arise because each institution has its specific legislation, such as the Normative Instruction 31 and the Civil Code, which are exclusively used by the INSS and the Labor Court, respectively. The data obtained from the analysis of the labor claims due to occupational accidents revealed a predominance of negative causal connections in all three institutions for the same claim (90.14% by the SESMT, 77.46% by the INSS, and 88.73% by the Labor Court). We also found a predominance of coincident causal connections for the same labor claims by all three institutions (they coincided in approximately 80% of the cases, i.e., they were either all positive or all negative). The INSS was found to establish the greatest number of positive causal connections. Moreover, there was a significant difference in the proportion of positive causal connections established by the SESMT. Judges justified their disagreement with the other causal connections by stating that they were based on two elements: culpability and time-bar. Conclusion: we found that the causal connection used by the three institutions are homonymous for three types of conclusions; and that, although they have a common legal base, they are also subjected to laws that are specific to each of the institutions. A greater harmonization of the dissonant causal connections established by the SESMT and the INSS could help reduce the number, especially in Labor Courts, of “empty claims” with no legal or technical substantiation that overload and burden the judiciary and pose a financial burden to the country.